The principle of proportionality of restrictions on human rights and freedoms - Vasilevich, Sergey G. (Journal of the Belarusian State University. Law, 2024)
The article is devoted to the of the principle of proportionality of restriction on human rights and freedoms analysis. Doctrinal sources, as well as legislation are analysed. Attention is drawn to the need of definition of the concepts «law» and «legitimate aims». It is expressed that taking into account the existing practice of Belarus, in the context of Art. 23 of the Constitution of the Republic of Belarus the concept «law» should be considered in a broad aspect, including all legislative acts, as well as, taking into account the acts of the All-Belarusian People’s Assembly.
Keywords: restrictions on rights; law; legitimate aims